Measuring Welfare Gains from Better Quality Infrastructure - Klytchnikova, Irina; Lokshin, Michael (World Bank, Washington, DC, 2012)
Projects and reforms targeting infrastructure services can affect consumer welfare through changes in the price, coverage, or quality of the services provided. The benefits of improved service quality-while significant-are often overlooked because they are difficult to quantify. This paper reviews methods of evaluating the welfare implications of changes in the quality of infrastructure services within the broader theoretical perspective of welfare measurement. The study outlines the theoretical assumptions and data requirements involved, illustrating each method with examples that highlight common methodological features and differences. The paper also presents the theoretical underpinnings and potential applications of a new approach to analyzing the effects of interruptions in the supply of infrastructure services on household welfare.